Reliable Detection of Mismatch Repair Deficiency in Colorectal Cancers Using Mutational Load in Next-Generation Sequencing Panels - Stadler, Zsofia K; Battaglin, Francesca; Middha, Sumit; Hechtman, Jaclyn F; Tran, Christina; Cercek, Andrea; Yaeger, Rona; Segal, Neil H; Varghese, Anna M; Reidy-Lagunes, Diane L; Kemeny, Nancy E; Salo-Mullen, Erin E; et al. (Journal of clinical oncology, 2016)
Tumor screening for Lynch syndrome is recommended in all or most patients with colorectal cancer (CRC). In metastatic CRC, sequencing of RAS/BRAF is necessary to guide clinical management. We hypothesized that a next-generation sequencing (NGS) panel that identifies RAS/BRAF and other actionable mutations could also reliably identify tumors with DNA mismatch repair protein deficiency (MMR-D) on the basis of increased mutational load. We identified all CRCs that underwent genomic mutation profiling with a custom NGS assay (MSK-IMPACT) between March 2014 and July 2015. Tumor mutational load, with exclusion of copy number changes, was determined for each case and compared with MMR status as determined by routine immunohistochemistry. Tumors from 224 patients with unique CRC analyzed for MMR status also underwent MSK-IMPACT. Thirteen percent (n = 28) exhibited MMR-D by immunohistochemistry. Using the 341-gene assay, 100% of the 193 tumors with < 20 mutations were MMR-proficient. Of 31 tumors with ≥ 20 mutations, 28 (90%) were MMR-D. The three remaining tumors were easily identified as being distinct from the MMR-D tumors with > 150 mutations each. Each of these tumors harbored the P286R hotspot POLE mutation consistent with the ultramutator phenotype. Among MMR-D tumors, the median number of mutations was 50 (range, 20 to 90) compared with six (range, 0 to 17) in MMR-proficient/POLE wild-type tumors (P < .001). With a mutational load cutoff of ≥ 20 and < 150 for MMR-D detection, sensitivity and specificity were both 1.0 (95% CI, 0.93 to 1.0). A cutoff for mutational load can be identified via multigene NGS tumor profiling, which provides a highly accurate means of screening for MMR-D in the same assay that is used for tumor genotyping.